A Saccharide Chemosensor Array Developed Based on an Indicator Displacement Assay Using a Combination of Commercially Available Reagents - Sasaki, Yui; Zhang, Zhoujie; Minami, Tsuyoshi (Frontiers in Chemistry, 2019)
Herein, a very simple colorimetric chemosensor array is reported for saccharides (D-glucose, D-fructose, D-xylose, D-galactose, D-mannose, L-rhamnose and N-acetyl-D-gluosamine). While various types of chemosensors for saccharides have been investigated extensively to-this-date, tremendous additional efforts are still required on a regular basis for the syntheses of new chemosensors. Complicated syntheses would be a bottleneck given that artificial receptor-based chemosensing systems are not so popular in comparison to biomaterial-based (e.g., enzyme-based) sensing systems. Toward this end, chemosensor array systems using molecular self-assembled materials can avoid the abovementioned synthetic efforts and achieve simultaneous qualitative and quantitative detection of a number of guest saccharides. Using a practical approach, we focus on an indicator displacement assay to fabricate a chemosensor array for colorimetric saccharide sensing. On the basis, 3-nitrophenylboronic acid (3-NPBA) spontaneously reacts with catechol dyes such as alizarin red S (ARS), bromopyrogallol red (BPR), pyrogallol red (PR), and pyrocatechol violet (PV), and yields boronate ester derivatives with color changes. The addition of saccharides into the aqueous solution of the boronate esters induces color recovery owing to the higher binding affinity of 3-NPBA for saccharides, thus resulting in the release of dyes. By employing this system, we have succeeded in discriminating saccharides qualitatively and quantitatively with a classification success rate of 100%. Most importantly, our chemosensor array has been fabricated by only mixing low cost commersially available reagents in situ, which means that complicated synthetic processes are avoided for saccharide sensing. We believe that this simple colorimetric assay that uses only commercially available reagents can create new user-friendly supramolecular sensing pathways for saccharides.